The impact of the university education and knowledge transfer index on the global competitiveness of the United Arab Emirates from the perspective of quality employees - Mahdi, Shawk Hasan (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aimed to demonstrate the impact of the university education and knowledge transfer index on the global competitiveness of the United Arab Emirates from the point of view of quality employees. The study relied on the quantitative descriptive survey method. The tool was a questionnaire for data analysis. The study sample consisted of a group that was distributed to a sample of (330) of (director, executive director, head of department/division, employee) who work in departments, departments, and offices of quality management and academic accreditation in accredited higher education institutions. The sample size was (360) individuals. The sample size was calculated to find the number of individuals based on the equation Determine the size of the statistical sample for an unknown statistical population at the level of (0.05), where (360) questionnaires were distributed to the study sample, and (340) were retrieved. After examining the questionnaires, (330) questionnaires were found valid for analysis with a percentage of (91.6%), and the analysis was done by testing the hypotheses using Appropriate statistical methods from the Statistical Package for the Social Sciences (SPSS). The study reached several results, the most important of which is that the dimension of quoting and representing knowledge obtained an average degree of importance amounting to (3.55), that there is a statistically significant effect at a significant level (0.05 ≥ α) of knowledge transfer in competitiveness, represented by its combined dimensions for the United Arab Emirates, and the relationship between the two variables. It was expulsive; The coefficient of determination (R²) amounted to (25.3%) of the change in competitive ability, represented by its combined dimensions. This explains that the citation dimension positively affects the dependent variable, competitive ability, represented by its combined dimensions. The study recommended the need for the university to cooperate with local and Arab business institutions to offer distinguished specializations, and for the university to direct scientific research to faculty members to solve community problems and issues.